National Early Warning Score (NEWS) Outperforms Quick Sepsis-Related Organ Failure (qSOFA) Score for Early Detection of Sepsis in the Emergency Department - Dimitri Durr; Tapio Niemi; Jeremie Despraz; Selin Tusgul; Fabrice Dami; Rachid Akrour; Pierre-Nicolas Carron; Marie-Annick Le Pogam; Thierry Calandra; Sylvain Meylan (MDPI AG, 2022)
Background: Prompt recognition of sepsis is critical to improving patients' outcomes. We compared the performance of NEWS and qSOFA scores as sepsis detection tools in patients admitted to the emergency department (ED) with suspicion of sepsis. Methodology: A single-center 12-month retrospective study comparing NEWS using the recommended cut-off of ≥5 and qSOFA as sepsis screening tools in a cohort of patients transported by emergency medical services (EMS) to the Lausanne University Hospital (LUH). We used the Sepsis-3 consensus definition. The primary study endpoint was the detection of sepsis. Secondary endpoints were ICU admission and 28-day all-cause mortality. Results: Among 886 patients admitted to ED by EMS for suspected infection, 556 (63%) had a complete set of vital parameters panel enabling the calculation of NEWS and qSOFA scores, of whom 300 (54%) had sepsis. For the detection of sepsis, the sensitivity of NEWS > 5 was 86% and that of qSOFA ≥ 2 was 34%. Likewise, the sensitivities of NEWS ≥ 5 for predicting ICU admission and 28-day mortality were higher than those of qSOFA ≥ 2 (82% versus 33% and 88% versus 37%). Conversely, the specificity of qSOFA ≥ 2 for sepsis detection was higher than that of NEWS ≥ 5 (90% versus 55%). The negative predictive value of NEWS > 5 was higher than that of qSOFA ≥ 2 (77% versus 54%), while the positive predictive value of qSOFA ≥ 2 was higher than that of NEWS ≥ 5 (80% versus 69%). Finally, the accuracy of NEWS ≥ 5 was higher than that of qSOFA ≥ 2 (72% versus 60%). Conclusions: The sensitivity of NEWS ≥ 5 was superior to that of qSOFA ≥ 2 to identify patients with sepsis in the ED and predict ICU admission and 28-day mortality. In contrast, qSOFA ≥ 2 had higher specificity and positive predictive values than NEWS ≥ 5 for these three endpoints.